Ekspresja białek Bcl-2, Bcl-xl, Bak i Bax w aksonach nerwu wzrokowego u chorych z jaskrą dokonaną - Zalewska, Renata; Reszeć, Joanna; Mariak, Zofia; Sulkowski, Stanisław (Klinika Oczna / Acta Ophthalmologica Polonica, 2004)
Purpose: The aim of our study was the evaluation of Bcl-2, Bcl-xl, Bak and Bax immunoexpression in axons of the optic nerve with absolute glaucoma. Material and methods: This study was conducted on 19 patients with absolute glaucoma, suffered from severe ophthalmalgia, treated of necessity by enucleation in 1991-2003 in our Department of Ophthalmology. The samples were immuno-stained with antibodies for Bcl-2, Bak, Bax and Bcl-xl protein. The reactions were performed in Labelled Streptavidin Avidin Biotin (LSAB) technique. The evaluation of immuno-staining was calculated as the percentage of cells with positive reaction to the total number of cells encountered in 10 representative fields, by light microscopy using a x 20 objective lens. Scores were based on the following scale: (++), over 50% of the field showing positive immuno-staining, (+) 10-50% with positive immunostaining. Results: In our study proapoptotic Bak and Bax protein expression was stronger than antiapoptotic Bcl-2, Bcl-xl protein expression; Bak/Bcl-2 (p = 0,008), Bax/Bcl-2 (p = 0,0007), Bak/Bcl-xl (p = 0,0356), Bax/Bcl-xl (p = 0,0077). Conclusions: The results of our study demonstrate high proapoptotic trends in axons of the optic nerve in the stage of absolute glaucoma.